Fundamentals of Entrepreneurship ETR300: Kenyalang Recycling Centre / Cyrilla Bintang Issac ...[et al.] - Issac, Cyrilla Bintang; Alvin, Anthea Tessa; Simeon, Caius Graham; Caspar, Pilemon (2010)
The name of our company is Kenyalang Recycling Centre. The business is in form of enterprise which consists of four members. Each partner contributes certain amount of capital as agreed in agreement. The main business activity is dealing and managing recyclable waste materials by recycling the materials. We do deals with paper, aluminum cans and plastic. We also manage our business by collecting unwanted materials that can be recycled within Kuching and Kota Samarahan areas. These concepts are established due to the modern contemporary style of living which the people in this global era become busier with their work and neglecting the importance of recycling. Our concept is also accurate and suitable with the way of life which the community nowadays does not have much time to do recycling and our environment is affected. Our business operation is at 8 a.m to 5.30 p.m on weekdays, 8 a.m to 1 p.m on Saturday and closed on Sunday and public holidays. There are no sleeping partners and all are entitled to participate in the business management. We agreed that Cyrilla Bintang Issac is our General Manager and Administration Manager, Anthea Tessa Alvin Nagum as Marketing Manager, Pilemon Caspar Sambang as Operation Manager, and Caius Graham Simeon as Financial Manager. The selection of General Manager is based on consensus among all the partners and selected based on the experience, skills and ability.